Pembuatan handout mobile learning berbasis android untuk pembelajaran fisika pada materi gerak parabola dan gerak melingkar di kelas X SMA/MA - Muhammad Prisma; Festiyed Festiyed; Desnita Desnita; Silvi Yulia Sari (PILLAR OF PHYSICS EDUCATION, 2020)
This research was conducted because the learning process in the classroom was not yet using smartphone technology based on the curriculum 2013 revision. Each student has a smartphone device which is most are android, but they did not use it in the learning process, the teaching system using speech method, while the printed books still existing in the class. The usage ICT such as text, picture, sound, animation,and video in the class are in separated form yet. Therefore, the purpose of this research is to produce Handout based mobile learning assisted by android aplication and to know the validity criteria of the product. This variety of research is a mixed method. The research uses a validity test instrument that contains 4 aspects as follows; substances; language; graphic and utilization of software. The result are presented in the table,diagram and then analyzed to determine the advisability criteria of handout. Based on the research conducted, there are two results research obtained, first is the handout product are consisted of text, sound, picture, animation, and video while the second is the results of the validity test conducted twice, with an average value of the first validity is 86.93% with high valid criteria and the average value of the second validity is 94.49% with high valid criteria. Based on the results, it can be concluded that the product of handout mobile learning on parabolic and circular motion material assisted by the android class X SMA/MA is feasible to be used in the learning process.